Resolution of paraneoplastic hypoglycemia following nephroureterectomy for treatment of canine renal cell carcinoma: Case report - Huerta, Yael; Lenz, Jennifer; Flesner, Brian; Abrams, Brittany; Amerman, Hayley; Griffin, Maureen (Frontiers in Veterinary Science, 2023)
Objectives: To describe the clinicopathologic findings, imaging results, surgical treatment, and outcome of a dog with renal cell carcinoma (RCC) and paraneoplastic hypoglycemia. Animals: A 13-year-old female spayed mixed breed dog that was presented for facial twitching and neurologic decline and diagnosed with a renal mass and paraneoplastic hypoglycemia. Study design: Case report. Methods: Serum chemistry revealed severe hypoglycemia and normal renal values. Abdominal ultrasonography showed a large, heterogeneous, cavitated mass associated with the left kidney and no evidence of abdominal metastatic disease. Thoracic radiographs revealed no evidence of pulmonary metastatic disease. Fasted serum insulin was low concurrently with severe hypoglycemia. No other causes of hypoglycemia were detected, and paraneoplastic hypoglycemia was suspected. Results: After initial medical management of the dog’s hypoglycemia, left nephroureterectomy was performed. Histopathology was consistent with RCC. Postoperatively, the dog’s hypoglycemia resolved, and supplementation was discontinued. The dog remained stable and was discharged from the hospital 3 days after surgery. At 2-week, 3-month, and 5-month follow up evaluations, the dog remained euglycemic, and no definitive evidence of disease progression was detected. Eight months postoperatively, the dog was euthanized due to decline in mobility. Necropsy and histopathology revealed cerebral and spinal cord multifocal myelin sheath dilation and two primary pulmonary carcinomas with no evidence of recurrence or metastasis of the RCC. Conclusion: Surgical treatment of RCC with subsequent resolution of paraneoplastic hypoglycemia has not previously been reported in veterinary medicine. In this dog, nephroureterectomy for RCC resulted in immediate and sustained resolution of paraneoplastic hypoglycemia.